Prevalence of Tooth Loss due to Periodontitis in Patients Visiting Tertiary Care Hospital - Thapa, Sachita; Rijal, Arjun Hari; Humagain, Manoj; Lamichhane, Simant; Bhusal, Sita (Journal of Nepalese Society of Periodontology and Oral Implantology, 2023)
Introduction: Epidemiological studies have been showing that caries is the main reason for tooth loss. But nowadays, it seems to show an increasing trend of tooth loss due to periodontal reasons rather than caries. The retention of natural teeth can improve the quality of life by maintaining the ability to chew and digest food. Thus, directly or indirectly periodontitis leading to tooth loss affects quality of life. Objective: To determine the prevalence of tooth loss in periodontitis patients. Methods: A cross-sectional study was done in Department of Periodontology and Oral Implantology from June 2023 to September 2023 after obtaining ethical clearance from institutional review committee. Study participants were patients diagnosed as periodontitis according to world workshop in periodontics 2017 classification and prevalence of tooth loss was recorded according to the history of mobile tooth. Poor prognosis and hopeless prognosis were counted as to be extracted tooth in the study. Collected data were entered into the excel sheet and further statistical analysis was done using SPSS v.20. Results: Mean of tooth loss due to periodontitis was found to be 3.74±3.285 and tooth to be extracted is 1.94±1.884. Conclusion: As the age increases number of tooth loss increases, likewise current smokers have more amount of tooth loss than that of former and nonsmokers. Likewise, mandibular anterior region was most common for prevalence for tooth loss.